2004
DOI: 10.1039/b316810g
|View full text |Cite
|
Sign up to set email alerts
|

Vapor phase Beckmann rearrangement using high silica zeolite catalyst

Abstract: Vapor phase Beckmann rearrangement of cyclohexanone oxime to e-caprolactam has been studied using high silica zeolite catalysts. Catalysts with different crystal sizes and gel-ageing times have been activated by ionic exchange in different conditions by means of a highly basic solution and a nearly neutral solution both containing ammonium salts. Samples have been calcined at different temperatures in order modify the number of defective sites. We observed that samples exchanged by means of a highly basic solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 12 publications
(13 reference statements)
2
36
0
Order By: Relevance
“…S5). Two broad resonance signals are observed with chemical shifts at −113 and −103 ppm, which belong to SiO 4 groups and nest of silanols or bridged silanols, respectively [22].…”
Section: Resultsmentioning
confidence: 99%
“…S5). Two broad resonance signals are observed with chemical shifts at −113 and −103 ppm, which belong to SiO 4 groups and nest of silanols or bridged silanols, respectively [22].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the weakly acidic silanol groups on the surface of silica have been previously recognized as capable of assisting various reactions. [23,[45][46][47][48][49] To test the participation of silanol groups in the catalytic process, we treated MAP-MSN-3.5 with hexamethyldisilazane (HMDS). 29 Si NMR showed that this reduced the number of silanols by 39% (from 3.8 to 2.3 mmol/g, Figure 4).…”
Section: Cooperative Effects Of the Supportmentioning
confidence: 99%
“…No peaks corresponding to Na-containing phases were detected. All samples show reflections at 2θ = 24.4°, indicating that the typical structures of S-1-Na-x have monoclinic symmetry [8,14]. The relative crystallinity of the base treated S-1-Na-x samples were calculated by comparing the total intensity values for the peaks at 2θ = 7.9°, 8.9°, 23.0°, 23.2°, 23.7°a nd 24.0° [39] and assuming that those of S-1-Na-0 represent 100%.…”
Section: Characterization Of the Samplesmentioning
confidence: 98%
“…Molecular sieves have also been widely investigated for this reaction [3,. Among these, MFI-type zeolites [8][9][10][11][12][13][14][15][18][19][20][21][23][24][25]28,32] with high Si/Al ratios and silicalite-1 (S-1) have been found to be active and selective for this reaction. Sumitomo Chemical Co., Ltd. has commercialized the vapor phase Beckmann rearrangement of cyclohexanone oxime using S-1 as the catalyst [23].…”
Section: Introductionmentioning
confidence: 99%